2005
DOI: 10.1111/j.1365-2362.2005.01508.x
|View full text |Cite
|
Sign up to set email alerts
|

Heightened levels of circulating 20S proteasome in critically ill patients

Abstract: Detection of 20S proteasome may represent a novel marker of immunological activity and muscle degradation in sepsis and trauma patients, and may be useful in monitoring the clinical effect of proteasome-inhibitors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
59
0
3

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(66 citation statements)
references
References 22 publications
4
59
0
3
Order By: Relevance
“…Thus, the origin, the cellular extrusion mechanism(s), and the functions of extracellular, circulating proteasomes remain enigmatic. Nevertheless, their concentration is a useful diagnostic criterion for disease activity in patients with various illnesses (2)(3)(4)(5)(6). Our investigation showed that the pattern of subtypes of circulating proteasomes is changed in patients with SLE and RA compared with controls, and this change may somehow reflect the disease state of the donors and may be the basis for development of a new diagnostic test system to detect disease and monitor therapy.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…Thus, the origin, the cellular extrusion mechanism(s), and the functions of extracellular, circulating proteasomes remain enigmatic. Nevertheless, their concentration is a useful diagnostic criterion for disease activity in patients with various illnesses (2)(3)(4)(5)(6). Our investigation showed that the pattern of subtypes of circulating proteasomes is changed in patients with SLE and RA compared with controls, and this change may somehow reflect the disease state of the donors and may be the basis for development of a new diagnostic test system to detect disease and monitor therapy.…”
Section: Discussionmentioning
confidence: 85%
“…High-resolution anion exchange chromatography (in conjunction with a SMART chromatography system; Amersham Biosciences) was used to separate 20S proteasome subtypes on a Mini Q anion exchange column equilibrated with TEAD buffer as described elsewhere (6 ).…”
Section: Analysis Of Proteasome Subtypesmentioning
confidence: 99%
See 1 more Smart Citation
“…20S proteasomes are also detectable in healthy serum and plasma, and elevated circulating 20S proteasome (c20S) concentrations have been described in several diseases, such as hematologic malignancies, sepsis, trauma, and autoimmune diseases including systemic lupus erythematosus (SLE) (5,13,15,16). Although evidence for the functional role of c20S has not yet been provided, systemic concentrations of c20S are thought to reflect cellular damage and immunological activity.…”
mentioning
confidence: 99%
“…A small case-control study of critically ill patients found signifi cantly higher serum levels of 20S proteasome in 15 patients admitted to the ICU with a diagnosis of sepsis and 13 with a diagnosis of trauma compared with 15 patients admitted for elective abdominal surgery and 15 healthy volunteers. 79 A mouse model of sepsis found that infusion of the proteasome inhibitor MG-132 signifi cantly dampened tumor necrosis factor-a , IL-1, and IL-10 levels and prolonged survival compared with placebo. 80 This fi nding may suggest that circulating proteasome interacts with the infl ammatory response in sepsis, implying that the proteasome may have important immunomodulatory functions in patients with critical illness such as sepsis.…”
Section: Extracellular Proteasome Function In Sepsis and Alimentioning
confidence: 99%